Effect of Synthetic Fertilizer on Diazotrophic Bacteria in Secondary Forest and Oil Palm Soils in Central Kalimantan - Agustina, Delia; Purnamasari, Maria Indah; Karmawan, Listya Utami; Suwanto, Antonius (HAYATI Journal of Biosciences, 2025)
Soil microorganisms, especially diazotrophic bacteria, are vital for ecosystem sustainability, significantly contributing to nitrogen cycling and biodiversity conservation. Understanding the impact of different land-use practices on soil microorganisms, especially synthetic fertilizer addition, is essential for sustainable agriculture. This study compares soil properties, bacterial densities, and responses to fertilization in secondary forest soils and adjacent oil palm plantation soils located in PT Kerry Sawit Indonesia, Central Kalimantan. A greenhouse experiment was conducted using both secondary forest and oil palm plantation soils to evaluate the impacts of different synthetic fertilizers on nitrogen-fixing bacteria and soybean agronomic performance. Total soil bacteria and diazotrophic bacteria, essential for nitrogen fixation, were analyzed through microbiological assays and qPCR focusing on the nifH gene. Our findings show that oil palm plantation soils had higher levels of nitrogen, phosphate, and nitrate, while secondary forest soils had a higher abundance of diazotrophic bacteria. Furthermore, excessive nitrogen fertilization was found to reduce microbial density, negatively impacting plant sustainability, highlighting the importance of customized fertilizer management. The study highlights the intricate connections between land-use practices and microbial populations, providing valuable insights for balancing agricultural productivity with ecological sustainability.